Social Control, Trade Openness and Human Trafficking - Jiang, Bo (Journal of quantitative criminology, 2017)
Objective: Human trafficking has generated growing concern among both policy makers and researchers. However, research has been hampered by a lack of valid data and appropriate methods. Our study attempts to improve understanding of this issue by developing a macro-level social disorganization perspective which suggests that trade openness may be an important vector of human trafficking such that countries in transition between high and low levels are likely to face major challenges in controlling trafficking and will therefore be especially likely to experience high rates. Our analysis is based on United Nations panel data containing 163 time points for 43 countries from 2003 to 2008 where there is full information across the variables of interest. Methods: The study first relies on semi-parametric fixed effects regression estimators to determine the 'true' functional form of the relationship between trade openness and human trafficking. Next, we utilize random and fixed effects regression analysis and negative binomial regression analysis to assess the existence of an inverted U-relationship between trade openness and human trafficking. Results: Consistent with our theoretical prediction, the spline approximation of the relationship between trade openness and human trafficking rates exhibits a clear inverted-U. The random and fixed effects regression results support the same conclusion. The turning point is estimated to be 1.995 and two sensitivity analyses confirm this finding through a parametric and a nonparametric bootstrap method with replications. Finally, using negative binomial and fixed effects negative binomial regressions, we again confirm that there is an inverted-U relationship between trade openness and human trafficking counts. Conclusions: In line with a macro-level social disorganization perspective we argue that countries with relatively weak social control will have high rates of crime and deviance. We operationalize social control in terms of the openness of a country's trade to the international community and as expected we find a curvilinear relationship between levels of trade openness and human trafficking.